STUDI KINETIKA DEHIDRASI RISINOLEAT DARI MINYAK JARAK - Sitorus, M; Ibrahim, S; Nurdin, H; Darwis, D (Jurnal Riset Kimia, 2010)
ABSTRACT Dehydration of ricinoleic of castor oil into mixed of linoleic acid (LA) and conjugated linoleic acid (CLA) named DCO (dehydrated Castor Oil) was conducted by using P2O5 at temperature 125°C and 175°C were held time variety at 1, 2, 3 and 4 hour. Dehydration was maintained under reduced pressure 50 to 70 mmHg, gentle bubbling with Nitrogen , magnetically stirred between 800 to 1000 rpm and 0.1 g Zn powder as antipolymerization agent. The concentration changes of the ricinoleic and DCO followed by contrentation GC. The elucidation of ricinoleic, LA and CLA were analyzed by GC-MS. The result showed that reaction was first order with rate constant (k) was 1.0 × 10-2 h-1 at 125°C and 0.9631 h-1 at 175°C and energy of activation (Ea) was 191.152 kJmol-1and Keywords: Dehydration, Kinetic, Ricinoleic, LA and CLA.